Виготовлення витратних електродів з тугоплавких сполук для плавки у дуговій печі (огляд) - Степанчук, А.М. (Physico-technological Institute of Metals and Alloys, 2026)
The methods of obtaining consumable electrodes from some hard refractory carbides of transition metals of cylindrical shape with a ratio of length to diameter greater than 10 mm on their density and its distribution along the length of the electrode were analyzed. The data obtained during the study of the processes of obtaining electrodes from carbides of titanium, zirconium, niobium, chromium, molybdenum and tungsten, which are most widely used for the manufacture of powder products from them and the creation of wear-resistant coatings with their participation for multifunctional purposes, were analyzed. The conditions for obtaining electrodes by hot pressing, mouthpiece pressing, and pressing of blanks in a collapsible mold with subsequent sintering were considered. The influence of the method and modes of obtaining electrodes on their density, its distribution along the length was considered. The nature of these properties and the possibility of obtaining them with predetermined values are revealed. The influence of the method and modes of obtaining electrodes on their operational properties, in particular heat resistance, which is a defining requirement for electrodes, is also considered. High heat resistance ensures a stable melting process and the production of castings with a uniform distribution of the content of the casting components and structure. A mechanism for the formation of high heat resistance is proposed, which consists in the presence of porosity evenly distributed over the volume in the electrodes. The optimal conditions for obtaining electrodes that provide the greatest thermal stability have been established. It has been shown that the highest values are obtained for electrodes with a uniform density distribution along the length and a porosity of 10–15 %. The most suitable methods for manufacturing electrodes are die pressing and pressing in collapsible molds with subsequent sintering.